The impacts of lockdown restrictions on children's and adolescents' physical activity levels and sedentary behaviour including gender differences: A systematic review and meta-analysis - Li, Tianwei; Wang, Lei; Yu, Songmao (Quality in Sport, 2025)
The 2019 COVID-19 pandemic outbreak has caused a global public health emergency. In addition to preventing the spread of the disease, restrictions such as school closures may reduce children and adolescents' opportunities for physical activity and increase the prevalence of sedentary behaviour. However, the current evidence regarding the effects of COVID-19 on physical activity and sedentary behaviour in children and adolescents is insufficiently clear. A total of five databases were searched. In addition, grey literature, reference list and registries were also checked. A total of 26 studies were included in the systematic review. Total physical activity, moderate to vigorous physical activity, sedentary and ST were analysed separately using random effects models. Additionally, this study also used meta-analysis to investigate the differences between boys and girls, objective measures and subjective measures, cross-sectional studies and longitudinal studies. Results: The results of the meta-analysis showed that children and adolescents had a significant decrease in total physical activity (SMD= -0.76, 95% CI= -1.46 to -0.06, I2= 99.5%), moderate to vigorous physical activity (SMD= -0.36, 95% CI= -0.6 to -0.11, I2= 94.7%), sedentary behaviour (SMD= 1.44, 95% CI= 0.31 to 2.56, I2= 98.6%), and a significant increase in screen time (SMD= 0.75, 95% CI= 0.49 to 1.02, I2= 97.3%). Meta-analysis results showed a significant decline in moderate to vigorous physical activity in boys, but no change was found in girls. However, results from the systematic review suggested that girls are more likely to develop more screen time than boys. Children and adolescents' physical activity and sedentary behaviour are negatively impacted by restrictions associated with Covid-19. In addition, girls' screen time is more likely to increase than boys'.